THE RELATIONSHIPS BETWEEN CONDITIONS OF VEHICLE MAINTENANCE AND NUMBER OF CRANKSHAFT REVOLUTION OF ITS ENGINE - Liščák, Štefan; Drozdziel, Pawel (Doprava a spoje, 2005)
Basing on the analysis of the correlation between the number of 4CT90 engine crankshaft revolutions and distance covered by the LUBLIN truck between consecutive start-ups of its engine it was confirmed that during extra-urban conditions the work of an engine is more stable. The increase of the vehicle speed during "supervised" maintenance research causes the stabilization of engine work, too.